ERP أثرحوكمة تكنولوجيا المعلومات على جودة التقارير المالية عند تطبيق نظام تخطيط موارد المؤسسة - سعيد, پەیمان عثمان (Sulaimani Journal for Humanities, 2021)
The purpose of this research is to investigate the impact of information technology governance on the quality of financial reporting through the implementation of Performing Enterprise Resource Planning (ERP). Bazean Company for Cement is chosen as the sample of the study on the base of convenience sampling technique which is a type of non-probability sampling method. Primary data is collected through a structured questionnaire distributed among the employees of the sample company. The hypotheses of the study are tested using several statistical analysis methods. SPSS 24 is used in data analysis. The summary of the findings show that the observants generally agreed that technology governance and operating financial processes are associated with less time and lower cost. There is a moderate relationship between the importance of financial reporting quality that obtain from the application of ERP system and financial process in the least time and least cost and understanding the impact of information technology governance on the application of the enterprise resource planning system at 0.01 level. Therefore, the study provides significant insights to the managers of manufacturing companies about the significance of governance in selecting the factors that have impact on the success of ERP through the efficiency of technology and the quality of financial reporting to support senior management.
Keywords: Information Technology Governance; Financial Reporting; Enterprise Resource Planning